2021
DOI: 10.3390/su13063249
|View full text |Cite
|
Sign up to set email alerts
|

From Evidence to Design Solution—On How to Handle Evidence in the Design Process of Sustainable, Accessible and Health-Promoting Landscapes

Abstract: The work of landscape architects can contribute to the United Nation’s Sustainable Development Goals and the associated ‘Leave no one behind’ agenda by creating accessible and health-promoting green spaces (especially goals 3, 10 and 11). To ensure that the design of green space delivers accessibility and intended health outcomes, an evidence-based design process is recommended. This is a challenge, since many landscape architects are not trained in evidence-based design, and leading scholars have called for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The importance of urban green spaces for health and well-being have been well established (Chang et al 2021;Ayala-Azcárrag et al 2019;Gramkow et al 2021;Stier-Jarmer et al 2021). Moreover, research has demonstrated that people generally prefer and benefit from trees and other types of greenery in various situations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of urban green spaces for health and well-being have been well established (Chang et al 2021;Ayala-Azcárrag et al 2019;Gramkow et al 2021;Stier-Jarmer et al 2021). Moreover, research has demonstrated that people generally prefer and benefit from trees and other types of greenery in various situations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As we increasingly inhabit urban areas across the globe, this necessitates an enhanced understanding of the complexities of designing accessible public spaces (Imrie, 1996; Kajita, 2016) as an issue to be dealt with by practising landscape architects (Corazon et al. , 2019; Gramkow et al. , 2021).…”
Section: Accessibility a Professional Responsibility Of Landscape Arc...mentioning
confidence: 99%
“…As a result, physical spaces can determine whether a person with a particular health condition experiences a disability (Boys, 2014). As we increasingly inhabit urban areas across the globe, this necessitates an enhanced understanding of the complexities of designing accessible public spaces (Imrie, 1996;Kajita, 2016) as an issue to be dealt with by practising landscape architects (Corazon et al, 2019;Gramkow et al, 2021). With this in mind, previous research has criticised architecture and landscape architecture, claiming that the profession's accessibility solutions work primarily as "prosthetic devices" intended to address specific issues rather than to accommodate the bodily differences of human beings (Fitzsimons, 2017).…”
mentioning
confidence: 99%
“…In particular, knowledge 'transferability', 'aggregation', and 'appropriability' represent key features of such resources for SCA purposes, following the KBV [45]. Only very recently, the evidence-based knowledge approach has been adopted in relation to the focus on environmental preservation [46]. Stigsdotter and Sidenius [47] recommend an evidence-based design process model to ensure a design that supports health.…”
Section: -4-the Resource-based and Evidence-based Approachesmentioning
confidence: 99%
“…Their proposal is the Evidence-Based Health Design in Landscape (EBHDL) process model. The main benefits of this model are that it is user-centred, interdisciplinary, systematic, and transparent [46]. In such an approach, rather than the production of knowledge, priority should be placed on the collection of evidence, and then on "programming", "designing", and "evaluation".…”
Section: -4-the Resource-based and Evidence-based Approachesmentioning
confidence: 99%